A four-year follow-up of Caplan’s syndrome: A case report - Ling Wang; Yanling Liu; Yibin Zhang; Yue Hu (Journal of International Medical Research, 2025)
Caplan’s syndrome, also known as rheumatoid pneumoconiosis, is characterized by pulmonary nodules and rheumatoid arthritis in patients with pneumoconiosis. Owing to its low incidence rate and the presence of multiple nodules on lung computed tomography, it is often mistaken for other pulmonary diseases. Herein, we report the case of a 60-year-old man who presented to the hospital with joint edema and recurrent polyarthralgia. Laboratory studies revealed higher levels of rheumatoid factor and anti-citrullinated peptide antibodies, together with an enhanced erythrocyte sedimentation rate. Chest high-resolution computed tomography revealed multiple bilateral nodules during the evaluation for treatment contraindications. Based on the patient’s occupational background and findings from multidisciplinary consultations, a definitive diagnosis of Caplan syndrome was made. Maintenance therapy included low-dose methylprednisolone (gradually tapered and discontinued over 3 months), methotrexate, and hydroxychloroquine. The patient’s arthralgia and pulmonary nodules demonstrated stability over a follow-up period of up to 4 years, thereby indicating the success of this treatment.